The impact of participation in Diversity Field Fora on farmer management of millet and Sorghum varieties in Mali - Smale, Melinda; Diakité, L.; Sidibé, A.; Grum, M.; Jones, H.; Traoré, I.S.; Guindo. H.; Bioversity International (2011)
Malian farmers have been cultivating millet and sorghum for millennia, but they are slow to adopt and develop modern varieties because it is difficult to observe the difference in yields in their fields, given the challenging local growing conditions. Farmer participatory approaches are therefore recommended. This paper applies an instrumental variables method to survey data from Mali to evaluate the impacys of Diversity Field Fora, a type of farmer field school which aims to boost millet and sorghum yields by showing farmers how to manage diverse varieties. Impact indicators are expected and recalled millet and sorghum yields. the total number of unique attributes of millet and sorghum varieties stocked as seed, and the relative deprivation of the household farm with respect to these indicators. The findings suggest the project has had results at one of two sites where it has been implemented with the same local leadership and more intensively over a longer time frame.